Process for directly producing high-purity tantalum oxide from low-concentration tantalum solution
Patent Information
- Application Number
- CN202611402184.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-10-27
AI Technical Summary
若将此低浓度钽液直接进行中和沉淀制取氢氧化钽,即便钽液中某种杂质含量仅有1ppm,经中和沉淀后,得到的氧化钽中该杂质的富集也会超过200ppm,严重影响产品质量
1、通过“先提浓、后萃取净化”的工艺路线,使低浓度钽液(<5g/L)中的杂质在最终氧化钽产品中的含量降低至原有水平的1/20以下,产品纯度达到99.99%以上,解决了长期以来铌铁矿来源钽液只能生产普通级或次品氧化钽的技术难题;
Smart Images

Figure CN122977443A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrometallurgical materials technology, and in particular to a process for directly producing high-purity tantalum oxide from low-concentration tantalum liquid. Background Technology
[0002] High-purity tantalum oxide (Ta2O5) is an important raw material for producing high-value-added products such as tantalum powder, tantalum capacitors, and optical glass modifiers, and is widely used in electronics, chemicals, optics, and other fields. The existing mature method for producing high-purity tantalum oxide is solvent extraction. Its basic process flow is as follows: the raw ore is acid-leached to dissolve the effective components in an aqueous solution. Then, extraction is performed in a mixed clarification tank, using an extractant to extract both tantalum and niobium from the aqueous solution. A small amount of impurities on the extract is then washed away with dilute sulfuric acid. The extract solution containing tantalum and niobium is then back-extracted with a niobium-removing agent, allowing niobium to enter the aqueous phase, forming a niobium solution, which is used to produce high-purity niobium oxide. The remaining extractant contains only tantalum, which is then back-extracted with a tantalum-removing agent to obtain a tantalum solution, which is then used to produce high-purity tantalum oxide.
[0003] In the aforementioned production process, the quality of high-purity tantalum oxide is primarily determined by the completeness of impurity removal in the extraction stage and the thorough separation of tantalum and niobium. However, the anti-tantalum stage often requires a larger flow rate of anti-tantalum agent than the organic phase to ensure complete tantalum back-extraction, resulting in a lower concentration of the tantalum solution. This is especially true when using niobite as a raw material, where the tantalum content is extremely low, often resulting in a tantalum solution with a tantalum content of less than 5 g / L. If this low-concentration tantalum solution is directly neutralized and precipitated to produce tantalum hydroxide, even if a certain impurity in the solution is only 1 ppm, after neutralization and precipitation, the enrichment of that impurity in the resulting tantalum oxide will exceed 200 ppm, severely impacting product quality. Therefore, when niobite is used as a raw material in the industry, the resulting tantalum oxide is typically sold as ordinary tantalum oxide or a substandard product, or it needs to be reused as raw material for another production process to produce a high-purity product, resulting in low production efficiency and high costs.
[0004] To address the aforementioned issues, some existing technologies attempt to improve the purity of tantalum solution through multiple extractions or flotation extraction. However, these methods still suffer from drawbacks such as complex processes, high equipment investment, and significant extractant loss. Furthermore, during the heating and concentration process of tantalum solution containing high concentrations of hydrofluoric acid, ordinary metal heat exchangers suffer from severe corrosion, and corrosion products contaminate the material. Conventional PTFE heat exchangers, on the other hand, suffer from problems such as difficulty in sealing and easy leakage at the connection between the PTFE tubes and the metal tube sheet due to the large difference in thermal expansion coefficients, making them unsuitable for continuous industrial production. Therefore, there is an urgent need for a process and supporting corrosion-resistant equipment that can efficiently and cost-effectively convert low-concentration tantalum solution directly into high-purity tantalum oxide.
[0005] Therefore, this invention proposes a process for directly producing high-purity tantalum oxide from low-concentration tantalum solution. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of existing technologies and to propose a process for directly producing high-purity tantalum oxide from low-concentration tantalum solution.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A process for directly producing high-purity tantalum oxide from low-concentration tantalum solution includes the following steps: Step S1, Concentration Step: The low-concentration tantalum solution is sent to a concentration device for heating and concentration treatment, so that the tantalum concentration in the tantalum solution is increased by more than 20 times, and the concentrated tantalum solution is obtained. The concentration device includes a corrosion-resistant heat exchanger for heating tantalum liquid; the corrosion-resistant heat exchanger is a shell-and-tube heat exchanger, with PTFE tubes on the tube side and 316L stainless steel on the shell side. The tube sheet is made of 316L stainless steel and lined with a silicon carbide anti-corrosion coating. An annular groove is provided at the connection between the tube sheet and the PTFE tubes. The end flange of the PTFE tube is embedded in the annular groove. The fasteners for spraying PTFE are bolts or studs, which pass through the tube sheet and press the PTFE tube flange to achieve sealing and fixation. Step S2, Extraction and Purification Step: The concentrated tantalum solution is subjected to countercurrent extraction with the extractant to remove impurities that are concentrated along with the tantalum solution, and a purified tantalum solution is obtained. Step S3, Neutralization and Precipitation Step: The purified tantalum solution is neutralized with a neutralizing agent to precipitate tantalum as tantalum hydroxide. After solid-liquid separation, tantalum hydroxide is obtained. Step S4, Calcination step: The tantalum hydroxide is calcined at high temperature to obtain a high-purity tantalum oxide product.
[0008] As a preferred technical solution of this application, the low-concentration tantalum solution is an anti-tantalum solution obtained by acid leaching, extraction, anti-niobium and anti-tantalum processes using niobium iron ore as raw material, and its tantalum content is less than 5g / L.
[0009] As a preferred technical solution of this application, the thickness of the silicon carbide anti-corrosion coating is 0.1 to 1.0 mm, and the surface of the PTFE-sprayed fastener is coated with a polytetrafluoroethylene coating with a thickness of 10 to 50 μm.
[0010] As a preferred technical solution of this application, in step S2, the extractant and the concentrated tantalum solution are subjected to countercurrent extraction at a ratio (organic phase: aqueous phase) of 1:1.5 to 1:5, and the number of extraction stages is 2 to 8.
[0011] As a preferred technical solution of this application, in step S3, the neutralizing agent is ammonia water, and the pH value at the neutralization endpoint is controlled at 8-10.
[0012] As a preferred technical solution of this application, in step S4, the calcination temperature is 800℃~1200℃ and the calcination time is 1~4 hours.
[0013] As a preferred technical solution of this application, in the final high-purity tantalum oxide product, the content of each impurity element is less than 1 / 20 of the corresponding impurity content in the tantalum oxide obtained by direct neutralization and precipitation of the low-concentration tantalum solution, and the purity of tantalum oxide is not less than 99.99%.
[0014] A corrosion-resistant heat exchanger for concentrating low-concentration fluorinated tantalum solution, wherein the heat exchanger is a shell-and-tube heat exchanger structure, and the tube-side channel is composed of PTFE tubes for flowing tantalum solution containing hydrofluoric acid. The shell-side passage is made of a 316L stainless steel shell and is used for the flow of the heating medium. The tube sheet uses a 316L stainless steel base, and its surface in contact with tantalum liquid is lined with a silicon carbide anti-corrosion coating. The connection between the tube sheet and the PTFE tube is provided with an annular groove. The end flange of the PTFE tube is embedded in the annular groove. The fasteners coated with PTFE are bolts or studs, which pass through the tube sheet and press the PTFE tube flange to achieve sealing and fixation.
[0015] As a preferred technical solution of this application, the thickness of the silicon carbide anti-corrosion coating is 0.1 to 1.0 mm, and the surface of the PTFE-coated fastener is coated with a PTFE layer with a coating thickness of 10 to 50 μm.
[0016] The beneficial effects of this invention are as follows: 1. By using the process route of "concentration first, extraction and purification later", the impurities in the low-concentration tantalum solution (<5g / L) are reduced to less than 1 / 20 of the original level in the final tantalum oxide product, and the product purity reaches more than 99.99%. This solves the long-standing technical problem that tantalum solution from niobium iron ore can only produce ordinary or substandard tantalum oxide. 2. By combining concentration and extraction purification steps, a significant synergistic effect is achieved: concentration creates favorable conditions for extraction purification, enabling efficient impurity removal with a small amount of extractant; while extraction purification effectively compensates for the shortcomings of simultaneous concentration of impurities during concentration. The results of the examples show that the total impurity content of the product obtained by concentration without extraction alone is approximately 8000 ppm, while the total impurity content drops sharply to below 78 ppm after concentration combined with extraction, demonstrating the non-obviousness of the synergistic effect. 3. To address the strong corrosiveness of tantalum hydrofluoric acid solution and the sealing challenges caused by the thermal expansion difference between PTFE tubes and metal tube sheets, a multi-layered corrosion-resistant heat exchanger was designed, consisting of PTFE tubes + 316L shell + silicon carbide coated tube sheet + annular groove flange embedding + PTFE-sprayed fasteners. The coordinated materials and sealing structure of each component ensure equipment durability while preventing secondary contamination of materials by corrosion products and leaks. Simultaneously, it solves the sealing failure problem caused by the thermal expansion difference between the PTFE tubes and metal tube sheet, ensuring reliable long-term continuous production. 4. The process of this invention is simple, the equipment investment is moderate, and the operation is convenient. It can directly utilize the tantalum liquid in the anti-tantalum section of the existing hydrometallurgical production line without the need for additional pretreatment processes, and has broad prospects for industrial application. Attached Figure Description
[0017] Figure 1 This is a process flow diagram for the direct production of high-purity tantalum oxide from low-concentration tantalum solution proposed in this invention. Detailed Implementation
[0018] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0019] I. Experimental Methods, Standards and Instruments Experimental methods Impurity element detection method: The content of each impurity element in tantalum oxide products was determined by inductively coupled plasma mass spectrometry (ICP-MS). After microwave digestion, the matrix effect was compensated by the standard addition method. The detection limits of each element were 0.001–0.1 μg / g, and the recoveries were 90%–115%.
[0020] Testing standards The analysis was performed in accordance with GB / T 15076 "Chemical Analysis Methods for Tantalum and Niobium" and YS / T 547-2007 "High Purity Tantalum Pentoxide".
[0021] Main instruments Inductively Coupled Plasma Mass Spectrometer (ICP-MS): ELAN DRC-e type; Microwave digestion system: BERGHOF MWS-3; Rotary tube furnace: Tubular rotary furnace, the furnace tube material is corundum, and the maximum operating temperature is ≥1200℃; Pure water machine: Milli-Q ultrapure water machine.
[0022] II. Examples and Comparative Examples Example 1 Raw materials: The anti-tantalum solution obtained from columbite ore through acid leaching, extraction, anti-niobium and anti-tantalum processes has a tantalum content of 4.2 g / L (calculated as Ta2O5). The main impurities are: Fe 2.8 mg / L, Mn 1.5 mg / L, Nb 3.2 mg / L, and Ti 0.9 mg / L.
[0023] The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution described in this embodiment includes the following steps: Step S1, Concentration Step: 1000L of the above-mentioned low-concentration tantalum solution is fed into a concentration device. The corrosion-resistant heat exchanger of this invention is used for heating and concentration. The heating medium is steam, and the evaporation temperature is controlled at 85-95°C. The concentration is increased to 50L of tantalum solution, and the tantalum concentration is increased to approximately 84g / L (concentration ratio approximately 20 times). The corrosion-resistant heat exchanger is a shell-and-tube structure, with PTFE tubes on the tube side, 316L stainless steel on the shell side, and a 316L substrate lined with a silicon carbide coating (coating thickness 0.5mm). An annular groove is provided at the connection between the tube sheet and the PTFE tube. The PTFE tube flange is embedded in the groove, and bolts coated with PTFE are tightened to achieve a seal. Step S2, Extraction and Purification Step: The concentrated tantalum solution is subjected to 5-stage countercurrent extraction with methyl isobutyl ketone (MIBK) extractant at a ratio (organic phase: aqueous phase) of 1:3 to obtain purified tantalum solution; Step S3, Neutralization and Precipitation: Slowly add ammonia to the purified tantalum solution, and control the final pH value to 9.0 under stirring conditions, so that tantalum precipitates out as tantalum hydroxide. Filter and wash the precipitate with pure water until neutral. Step S4, Calcination step: Calcinate tantalum hydroxide at 1000℃ for 2 hours, and obtain high-purity tantalum oxide product after cooling.
[0024] Example 2 Raw materials: Tantalum solution from the same batch as in Example 1, with a tantalum content of 4.1 g / L (calculated as Ta2O5), and the contents of the main impurities: Fe 2.7 mg / L, Mn 1.6 mg / L, Nb 3.1 mg / L, and Ti 0.8 mg / L.
[0025] The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution described in this embodiment includes the following steps: Step S1, Concentration Step: 1000L of low-concentration tantalum solution is fed into a concentration device and concentrated to a volume of 40L, increasing the tantalum concentration to approximately 102.5g / L (concentration factor of approximately 25 times). The corrosion-resistant heat exchanger structure is the same as in Example 1, with a silicon carbide coating thickness of 0.8mm and a PTFE-coated bolt coating thickness of 30μm.
[0026] Step S2, Extraction and Purification Step: The concentrated tantalum solution is subjected to 5-stage countercurrent extraction with tributyl phosphate (TBP) extractant at a ratio (organic phase: aqueous phase) of 1:2.5 to obtain purified tantalum solution.
[0027] Step S3, Neutralization and Precipitation: Slowly add ammonia to the purified tantalum solution, controlling the final pH value to 8.5, so that tantalum precipitates out as tantalum hydroxide, then filter and wash.
[0028] Step S4, Calcination step: Calcinate tantalum hydroxide at 900℃ for 3 hours to obtain high-purity tantalum oxide product.
[0029] Example 3 Raw materials: Tantalum liquid from the same batch as in Example 1.
[0030] The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution described in this embodiment includes the following steps: Step S1, Concentration Step: 1000L of low-concentration tantalum solution is fed into a concentration device and concentrated to a volume of 33L, increasing the tantalum concentration to approximately 127g / L (concentration factor approximately 30 times). The corrosion-resistant heat exchanger structure is the same as in Example 1, with a silicon carbide coating thickness of 0.3mm and a PTFE-coated bolt coating thickness of 20μm. Step S2, Extraction and Purification Step: The concentrated tantalum solution and 2-octanol extractant are subjected to 5-stage countercurrent extraction at a ratio (organic phase: aqueous phase) of 1:4 to obtain the purified tantalum solution. Step S3, Neutralization and Precipitation: Slowly add ammonia to the purified tantalum solution, control the final pH value to 9.5, so that tantalum precipitates out as tantalum hydroxide, filter, and wash. Step S4, Calcination step: Calcinate tantalum hydroxide at 1100℃ for 1.5 hours to obtain high-purity tantalum oxide product.
[0031] Comparative Example 1 Raw materials: Tantalum solution from the same batch as in Example 1 (tantalum content 4.2 g / L), without any concentration or extraction purification treatment.
[0032] The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution described in this comparative example includes the following steps: 1000L of low-concentration tantalum solution was directly added to the neutralization tank, and ammonia was slowly added to control the final pH value to 9.0, so that tantalum precipitated out as tantalum hydroxide. After filtration and washing, the tantalum hydroxide was calcined at 1000℃ for 2 hours to obtain tantalum oxide product.
[0033] Comparative Example 2 Raw materials: Tantalum liquid from the same batch as in Example 1.
[0034] The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution described in this comparative example includes the following steps: Step S1, Concentration Step: 1000L of low-concentration tantalum solution is fed into the concentration device and concentrated to a volume of 50L (concentration ratio of about 20 times).
[0035] Step S2, Neutralization and Precipitation: Add the concentrated tantalum solution directly to the neutralization tank, slowly add ammonia water, control the final pH value to 9.0, so that tantalum precipitates out as tantalum hydroxide, filter, and wash.
[0036] Step S3, calcination step: Calcine tantalum hydroxide at 1000℃ for 2 hours to obtain tantalum oxide product.
[0037] Comparative Example 3 Raw materials: Tantalum liquid from the same batch as in Example 1.
[0038] The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution described in this comparative example includes the following steps: Step S1, Concentration Step: 1000L of low-concentration tantalum solution is fed into the concentration device and concentrated to a volume of 200L (concentration ratio of only 5 times).
[0039] Step S2, Neutralization and Precipitation: Add the concentrated tantalum solution directly to the neutralization tank, slowly add ammonia water, control the final pH value to 9.0, so that tantalum precipitates out as tantalum hydroxide, filter, and wash.
[0040] Step S3, calcination step: Calcine tantalum hydroxide at 1000℃ for 2 hours to obtain tantalum oxide product.
[0041] III. Experimental Results and Analysis Table 1 Comparison of results between the examples and comparative examples
[0042] Results analysis: The experimental results above show that: 1. Comparative Example 1 directly used a low-concentration tantalum solution (tantalum content 4.2 g / L) for neutralization and precipitation. The resulting tantalum oxide product had a total impurity content as high as 15,000 ppm, with a purity of only 98.500%. Taking Fe as an example, the Fe content in the raw tantalum solution was only 2.8 mg / L, but after neutralization and precipitation, the Fe content in the product reached as high as 205 ppm, an enrichment of about 73 times. This indicates that when directly neutralized with a low-concentration tantalum solution, impurities precipitate simultaneously with tantalum and undergo severe enrichment, making it impossible to obtain a high-purity product. In contrast, Examples 1-3 of this invention, by concentrating the tantalum solution (20-30 times) and combining it with extraction purification, achieved a product purity of over 99.99%, and reduced the total impurity content to 42-78 ppm, only 0.28%-0.52% of Comparative Example 1, fully meeting the quality requirements for high-purity tantalum oxide.
[0043] 2. Comparative Example 2 only concentrated the tantalum solution 20 times without extraction purification. The total impurity content of the product was approximately 8000 ppm, which, although lower than Comparative Example 1, was still far above the high-purity product standard. This is because the concentration process simultaneously concentrates impurities while concentrating tantalum, resulting in a large amount of impurities still entering the precipitate phase during neutralization. In contrast, Example 1, with the same concentration factor (20 times), added an extraction purification step, and the total impurity content of the product plummeted to 78 ppm, only about 1% of Comparative Example 2. This indicates a significant synergistic effect between "concentration" and "extraction purification"—concentration creates more favorable conditions for extraction purification, enabling efficient impurity removal with a small amount of extractant; while the intervention of extraction precisely compensates for the defect of simultaneous impurity concentration during concentration. This synergistic effect was not expected by those skilled in the art, as conventional logic tends to "purify first, then concentrate" to avoid impurity concentration. This invention takes the opposite approach, achieving unexpected technical results.
[0044] 3. In Comparative Example 3, the tantalum solution was concentrated only 5 times before direct neutralization, resulting in a total impurity content of approximately 12,000 ppm in the product, showing limited improvement compared to Comparative Example 1 (unconcentrated). This indicates that the concentration factor needs to reach a certain threshold (such as more than 20 times as required by this invention) to create a sufficient concentration difference and comparative advantage for subsequent extraction and purification, thereby effectively reducing the impurity content of the product. The discovery of this critical value provides clear operational guidance for industrial production.
[0045] 4. In Examples 1-3, as the concentration factor increased from 20 times to 30 times, the total impurities in the product further decreased from 78 ppm to 42 ppm, and the purity increased accordingly. This indicates that, with the assistance of extraction and purification steps, an appropriate increase in the concentration factor helps to obtain a product with higher purity.
[0046] 5. After multiple batches of continuous operation in Examples 1-3, no corrosion leakage or sealing failure was observed in the corrosion-resistant heat exchanger, and the content of corrosive impurities such as iron in the material did not increase. This proves that the heat exchanger structure of the present invention effectively solves the problem of thermal expansion sealing between PTFE tubes and metal tube sheets, and prevents hydrofluoric acid from corroding metal components.
[0047] In summary, this invention, through a combination of "concentration + extraction purification" technology, successfully solves the technical problem of severe impurity enrichment during the direct neutralization and precipitation of low-concentration tantalum solution (<5g / L). This enables the direct production of high-purity tantalum oxide from niobium iron ore-derived tantalum solution, which could previously only be downgraded for sale. At the same time, it provides reliable corrosion-resistant heat exchange equipment, demonstrating significant industrial application value and inventiveness.
[0048] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A process for directly producing high-purity tantalum oxide from low-concentration tantalum solution, characterized in that, Includes the following steps: Step S1, Concentration Step: The low-concentration tantalum solution is sent to a concentration device for heating and concentration treatment, so that the tantalum concentration in the tantalum solution is increased by more than 20 times, and the concentrated tantalum solution is obtained. The concentration device includes a corrosion-resistant heat exchanger for heating tantalum liquid; the corrosion-resistant heat exchanger is a shell-and-tube heat exchanger, with PTFE tubes on the tube side and 316L stainless steel on the shell side. The tube sheet is made of 316L stainless steel and lined with a silicon carbide anti-corrosion coating. An annular groove is provided at the connection between the tube sheet and the PTFE tubes. The end flange of the PTFE tube is embedded in the annular groove. The fasteners for spraying PTFE are bolts or studs, which pass through the tube sheet and press the PTFE tube flange to achieve sealing and fixation. Step S2, Extraction and Purification Step: The concentrated tantalum solution is subjected to countercurrent extraction with the extractant to remove impurities that are concentrated along with the tantalum solution, and a purified tantalum solution is obtained. Step S3, Neutralization and Precipitation Step: The purified tantalum solution is neutralized with a neutralizing agent to precipitate tantalum as tantalum hydroxide. After solid-liquid separation, tantalum hydroxide is obtained. Step S4, Calcination step: The tantalum hydroxide is calcined at high temperature to obtain a high-purity tantalum oxide product.
2. The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution according to claim 1, characterized in that, The low-concentration tantalum solution is an anti-tantalum solution obtained by acid leaching, extraction, anti-niobium, and anti-tantalum processes using niobium iron ore as raw material, and its tantalum content is less than 5g / L.
3. The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution according to claim 1, characterized in that, The silicon carbide anti-corrosion coating has a thickness of 0.1 to 1.0 mm, and the fasteners coated with PTFE have a PTFE coating with a thickness of 10 to 50 μm.
4. The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution according to claim 1, characterized in that, In step S2, the extractant and the concentrated tantalum solution are subjected to countercurrent extraction at a ratio of 1:1.5 to 1:5, and the number of extraction stages is 2 to 8.
5. The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution according to claim 1, characterized in that, In step S3, the neutralizing agent is ammonia, and the pH value at the neutralization endpoint is controlled between 8 and 10.
6. The process for directly producing high-purity tantalum oxide from low-concentration tantalum solution according to claim 1, characterized in that, In step S4, the calcination temperature is 800℃~1200℃, and the calcination time is 1~4 hours.
7. A process for directly producing high-purity tantalum oxide from a low-concentration tantalum solution according to any one of claims 1-6, characterized in that, In the final high-purity tantalum oxide product, the content of each impurity element is less than 1 / 20 of the corresponding impurity content in the tantalum oxide obtained by direct neutralization and precipitation of the low-concentration tantalum solution, and the purity of tantalum oxide is not less than 99.99%.
8. A corrosion-resistant heat exchanger for concentrating low-concentration fluorinated tantalum solution, wherein the heat exchanger is a shell-and-tube heat exchanger structure, characterized in that: The tube-side channel is made of PTFE tubing and is used to flow tantalum liquid containing hydrofluoric acid; The shell-side passage is made of a 316L stainless steel shell and is used for the flow of the heating medium. The tube sheet uses a 316L stainless steel base, and its surface in contact with tantalum liquid is lined with a silicon carbide anti-corrosion coating. The connection between the tube sheet and the PTFE tube is provided with an annular groove. The end flange of the PTFE tube is embedded in the annular groove. The fasteners coated with PTFE are bolts or studs, which pass through the tube sheet and press the PTFE tube flange to achieve sealing and fixation.
9. The corrosion-resistant heat exchanger according to claim 8, characterized in that, The thickness of the silicon carbide anti-corrosion coating is 0.1 to 1.0 mm, and the surface of the PTFE-coated fastener is coated with a PTFE layer with a coating thickness of 10 to 50 μm.
10. The process according to claim 1, characterized in that, The corrosion-resistant heat exchanger is the corrosion-resistant heat exchanger as described in claim 8 or 9.